2020
DOI: 10.35595/2414-9179-2020-1-26-12-21
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment of the territories on the example of municipalities of the Smolensk region

Abstract: The article discusses the experience of environmental assessment at the global and regional levels. The methodology for assessing the environmental situation at the municipal level of the model research region — Smolensk region. To obtain the pollution index, we used indicators of emissions of pollutants into the atmosphere, the discharge of polluted wastewater and the generation of municipal solid waste. The choice of the first two indicators was determined by their impact on the health status of the populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…For calculation of the PHI, an evaluative algorithm was developed by one of the authors [ 49 ]. The normalization of initial indicators is achieved by the following formula: where is the worst value (for each indicator), in terms of the impact on the population health in the regions of Russia (the maximum infant mortality rate, lowest life expectancy);…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For calculation of the PHI, an evaluative algorithm was developed by one of the authors [ 49 ]. The normalization of initial indicators is achieved by the following formula: where is the worst value (for each indicator), in terms of the impact on the population health in the regions of Russia (the maximum infant mortality rate, lowest life expectancy);…”
Section: Methodsmentioning
confidence: 99%
“…The threshold followed by a sharp increase in heterogeneity can be optimally taken as the final number of clusters. The algorithm was originally described in [ 49 ] and has been tested in previous studies [ 30 , 40 , 50 ]. In this study, the dynamics of health status in Russia and in the world for 1990–2017 were revealed according to the calculation of the PHI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation